Contribution of the Two Types of Ekman Pumping Induced Eddy Heat Flux to the Total Vertical Eddy Heat Flux. Issue 9 (10th May 2021) - Li, Dapeng; Chang, Ping; Ramachandran, Sanjiv; Jing, Zhao; Zhang, Qiuying; Kurian, Jaison; Gopal, Abishek; Yang, Haiyuan
Abstract: Based on eddy‐rich (0.1° horizontal resolution for ocean) Community Earth System Model simulations, we compute the Ekman pumping induced vertical eddy heat flux using two formulations: the classical and the Stern‐Ekman pumping. The two mechanisms yield similar patterns in the eddy‐induced vertical heat flux, showing strong upward heat flux in ocean frontal regions such as the western boundary current regions. Using the Gulf Stream Extension region as an example, we estimate (1) the Stern‐Ekman pumping induced eddy heat flux is 23% and 12% of the total vertical eddy heat flux at 50 m depth during summer and winter, respectively; (2) the classical Ekman pumping accounts for 82% and 88% of the Stern‐Ekman pumping induced eddy heat flux at 50 m during summer and winter, respectively. The second finding indicates eddy current feedback on wind stress is the primary cause for the upward eddy heat flux generated by Ekman pumping. Plain Language Summary: The classical Ekman pumping is well‐known for its role in driving global ocean circulations. Stern‐Ekman pumping modifies the classical Ekman pumping by taking into consideration of ocean eddy vorticity. In this study, we investigate the Ekman pumping induced eddy vertical heat flux using the two formulations above. Based on an eddy‐rich climate model simulation, we find the eddy heat flux induced by the Stern‐Ekman pumping can account for ∼10%–20% the total vertical eddy heat flux at 50 m in eddy‐rich ocean frontal regions, such as the Antarctic circumpolar region and the subtropical western boundary current regions. Comparison of the two Ekman pumping formulations shows the classical Ekman pumping can account for the majority of the Stern‐Ekman pumping induced eddy heat flux, although the classical Ekman pumping generates much weaker vertical motions than the Stern‐Ekman pumping. The results of this work suggest that parameterizing vertical eddy heat flux within the upper ocean mixed layer should take into consideration of the wind‐forced eddy heat flux component. Key Points: In eddy‐rich ocean frontal regions, Ekman pumping can account for 10%–20% of vertical eddy heat flux at 50 m depth Eddy current feedback on wind stress is the key mechanism for Ekman pumping induced vertical eddy heat flux The results of this work suggest the wind‐forced vertical eddy heat transport should be considered in the submesoscale parameterization